2009
DOI: 10.1051/0004-6361/200811389
|View full text |Cite
|
Sign up to set email alerts
|

Molecular gas and a new young stellar cluster in the far outer Galaxy

Abstract: Aims. We investigate the star-formation ocurring in the region towards IRAS 07527-3446 in the molecular cloud [MAB97]250. 63-3.63, in the far outer Galaxy. We report the discovery of a new young stellar cluster, and describe its properties and those of its parent molecular cloud. Methods. Near-infrared JHK S images were obtained with VLT/ISAAC, and millimetre line CO spectra were obtained with the SEST telescope. VLA archive date were also used. Results. The cloud and cluster are located at a distance of 10.3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Interestingly, star formation occurs frequently and with no major differences in these edge environments, both in the far outer Galaxy (e.g. Brand & Wouterloot 2007;Yasui & Kobayashi 2008;Yun et al 2009), and also well below the Galactic plane as shown here. The relatively small number of molecular clouds at this large vertical distance (May et al 1997) do not appear to significantly affect the occurrence and properties of the star formation process.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Interestingly, star formation occurs frequently and with no major differences in these edge environments, both in the far outer Galaxy (e.g. Brand & Wouterloot 2007;Yasui & Kobayashi 2008;Yun et al 2009), and also well below the Galactic plane as shown here. The relatively small number of molecular clouds at this large vertical distance (May et al 1997) do not appear to significantly affect the occurrence and properties of the star formation process.…”
Section: Discussionsupporting
confidence: 63%
“…The only significant difference of these "edge" star formation sites is that they do not seem to form massive stars (e.g. Yun et al 2007Yun et al , 2009). In fact, based on the observed fluxes, no massive star is expected to be forming in this region.…”
Section: Discussionmentioning
confidence: 99%
“…That stars form at large galactocentric radii in MW like galaxies is supported by the discovery of young stellar clusters at larger Galactocentric distances (e.g. Caramazza et al 2008; Yun et al 2009) and ultraviolet (UV) observations by the GALEX satellite. The latter show evidence for extended UV emission presumably related to ongoing star formation and feedback from massive stars, at low rates, in those regions (Gil de Paz et al 2007).…”
Section: Resultsmentioning
confidence: 94%
“…Since the clump E is well-contained in our emission line maps, a comparison with CO-derived masses is possible provided we consider only the central pointing of the CO maps. Two methods can be exploited to compute mass estimates from our CO observations, as done, for example, in Yun et al (2009). Here, however, we want to consider the Gaussian profiles fitted to the wings of the self-absorbed observed lines as genuine recovered line profiles.…”
Section: The Herschel Viewmentioning
confidence: 99%
“…As part of our study of young embedded clusters in the outer Galaxy (e.g. Yun et al 2009;Palmeirim & Yun 2010), we have conducted observations (near-infrared JHKS imaging, and millimetre CO line) towards IRAS 04186+5143. These observations revealed the presence of a young stellar population embedded in a molecular cloud core.…”
Section: Introductionmentioning
confidence: 99%